2020 - A TIME OF CRISIS AND SOCIAL DISTANCING, PANDEMIC COVID-19 - TIME TO STRENGTHEN SCIENCE AND HOPE TO FACE LIFE - EDITORIAL - Carniatto, Irene; Alves, Gustavo Biasoli (International Journal of Environmental Resilience Research and Science, 2020)
Two thousand twenty was an awkward and challenging year. Snatched up by a virus, All of a sudden, we saw ourselves working at home. We were physically away from some of the ones we love and from a daily life we were already used to. We have been living a different and introspective year, with social distance under isolation and solitude. At this time, we had the opportunity to withdraw and rethink our purposes, attitudes, values, and our place in the world. We have the chance to think about the meaning of life, look around and see the relationships we have established with one another, with my brotherhood, and with all living and non-living beings that inhabit this planet, our “Common Home”. It is difficult to think of something more challenging and able to test our resilience! This is not only from a personal point of view, but also from a social, economic and environmental point of view. That is why it is important to talk about resilience, discuss it, test it, prove it and approve it. Such resilience has made us face this Pandemic - COVID-19 and fight for our existence, fight for health, look for respect, welcome and solidarity. Many were the examples of people and companies that helped with donations, delivered masks, hospital equipment, food and so on across all places and cities. But the challenges went further. Many hospital beds and ICUs had to be installed. Health professionals, doctors, nurses and so many others were had to and still face this struggle. They are anonymous generals in their barracks who fought this War of Death for Life. Unfortunately, not everyone could be saved from COVID. The number of those who were treated and recovered in Brazil was 6,501.341 people and 44,169.851 patients worldwide, considering this year, 2020. But 2020 will be remembered as a catastrophe and calamity, because despite efforts many fell down. The causalities’ numbers was in Brazil 188,259 and 1,722.307 in the world. An invaluable loss of human life. We also had other losses such as economic, environmental and social, especially in health. Many will be left with afterpains and a weakened wellbeing as a result of this virus infection; thus, it will not be possible to evaluate the extent of this problem. Many people have gotten worse or developed psycho-emotional pathologies such as depression, panic, among them, and their quality of life has been permanently affected. Many challenges since we have been living under a restricted mobility around the world, which had never been witnessed. There were empty streets, closed shops, bus stations and airports without people for several months. It should be told that political crises, the science negationism, discriminatory acts, polarization regarding data and fake news have exacerbated this crisis. A lot of misinformation, attacks on the environment and a sever backtracking of environmental protection laws and regulations, dismantling of environmental policies, fire was set in Amazon and in Midwestern Brazil that have reached the highest levels in centuries. A relatively large group of Brazilian citizens and in other countries who said they did not believe on how risky Corona virus could be. They neither believe in press information nor insisted on crowding in bars, streets and beaches, as soon as these spaces were opened. We consider unthinkable and even irrational attitudes with scientific knowledge nowadays, since they put their lives and the population’s at risk. Future is the judge of all actions, therefore, the results will be known only tomorrow. The researchers who make up the International Research Network on Climate Resilient Development - RIPEDRC have not faded! They proposed themselves to overcome this challenge of seeking resilience and sustainability! So, with Faith in our life ideals and in a superior motivation that guides our steps and makes us overcome challenges, we have launched to public notices, investigated, questioned and disseminated knowledge supported by several projects, live lectures, events and workshops. They created programs, joint projects and online platforms were developed. In Brazil, Paraguay and Argentina Trinational Border region, the Western Paraná State University - UNIOESTE, was in charge or partner of many efforts, among which we highlight two experiences that RIPEDRC Network participants took part.